Measuring corporate default risk - Duffie, Darrell (Oxford : Oxford University Press, 2011)
This examination of the empirical behaviour of corporate default risk provides a unified statistical methodology for default prediction based on stochastic intensity modelling. The findings are particularly relevant in the aftermath of the financial crisis.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Corporate debt -- Statistical methods; Corporate debt -- Mathematical models; Risk -- Statistical methods; Risk -- Mathematical models; Default (Finance) -- Statistical methods; Default (Finance) -- Mathematical models